Optimization of 2D photonic crystal waveguide using displacement and narrowing technique - Sharif, Nashad; Alam, Md. Mahbub (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2013.